Design development productivity of interior design-build firms before and during Covid-19 - Malana, Ma. Beatrice B. (College of Home Economics, University of the Philippines Diliman, 2023)
The study examined the design development productivity of six (6) purposively selected interior design-build firms in Metro Manila before and during COVID-19, in relation to communication, workload, and work execution time. It aimed to achieve specific objectives which were to describe the firms’ work operation setup, discuss their work systems, determine their design development productivity results before and during COVID-19, and assess how the new normal work systems have positively and negatively affected their design development productivity. The study was designed as qualitative-descriptive research and the researcher conducted two (2) techniques: (1) survey questionnaire and (2) online interview. Comparative-descriptive analysis was used for treatment of data. It was found that the majority of selected interior design-build firms transitioned to the work from home (WFH) setup during the pandemic. The survey questionnaire reflected a significant decrease in the design development productivity of the firms in terms of communication, workload, and work execution time due to lockdown restrictions, but contrasted the online interview responses. Two (2) out of six (6) firms answered that they were more productive during COVID-19, while another two (2) indicated that there was not much of a difference in their design development productivity between the two periods. The respondents expressed both positive and negative effects of the new normal work systems on their design development productivity. On the positive side, the majority of the firms indicated that the new normal work systems introduced various communication channels that made their workload lighter and work execution time quicker in accomplishing projects. However, for the other firms, due to lack of in-person interaction, there is still difficulty in material and furniture selection that cause delays in design approval.